Dialektika Dunia Facebook dalam Pemikiran Peter L Berger. Suatu Studi Tentang Filsafat Budaya - Tenau, Emanuel (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2018)
The world of facebook is the social phenomena of life in this era. Facebook does not only build a fraternal communication, but also has become a social problem. This essay tries to comprehend the dialectic phenomena of facebook from the phenomenological perspective of Peter L Berger. Berger perceives facebook as a dialectic process between the creator and the user of facebook or between the positive communication and the negative one. He looks into facebook in a systematic way with regard to dialectic relation between the structural fact and human act in reality. For Berger, facebook shows itself to the subject as it is, genuine, authentic, and there is no falsity. On the other hand, the user of facebook could exploit negatively for spreading hate. Dialectic of thefacebook world is exactly the social dynamic of our modern world.